Contribution of Connexin Hemichannels to the Decreases in Cell Viability Induced by Linoleic Acid in the Human Lens Epithelial Cells (HLE-B3) - Figueroa, Vania A.; Jara, Oscar; Oliva, Carolina A.; Ezquer, Marcelo; Ezquer, Fernando; Retamal, Mauricio A.; Martínez, Agustín D.; Altenberg, Guillermo A.; Vargas, Aníbal A. (Frontiers in Physiology, 2020)
Connexin (Cx) proteins form gap junction channels (GJC) and hemichannels that a allow bidirectional flow of ions and metabolites between the cytoplasm and extracellular space, respectively. Under physiological conditions, hemichannels have a very low probability of opening, but in certain pathologies, hemichannels activity can increase and induce and/or accelerate cell death. Several mechanisms control hemichannels activity, including phosphorylation and oxidation (i.e., S-nitrosylation). Recently, the effect of polyunsaturated fatty acids (PUFAs) such as linoleic acid (LA), were found to modulate Cxs. It has been seen that LA increase cell death in bovine and human lens cells. The lens is a structure allocated in the eye that highly depends on Cx for the metabolic coupling between its cells, a condition necessary for its transparency. Therefore, we hypothesized that LA induces lens cells death by modulating hemichannel activity. In this work, we characterized the effect of LA on hemichannel activity and survival of HLE-B3 cells (a human lens epithelial cell line). We found that HLE-B3 cells expresses Cx43, Cx46, and Cx50 and can form functional hemichannels in their plasma membrane. The extracellular exposure to 10–50 μM of LA increases hemichannels activity (dye uptake) in a concentration-dependent manner, which was reduced by Cx-channel blockers, such as the Cx-mimetic peptide Gap27 and TATGap19, La3+, carbenoxolone (CBX) and the Akt kinase inhibitor. Additionally, LA increases intracellular calcium, which is attenuated in the presence of TATGap19, a specific Cx43-hemichannel inhibitor. Finally, the long exposure of HLE-B3 cells to LA 20 and 50 μM, reduced cell viability, which was prevented by CBX. Moreover, LA increased the proportion of apoptotic HLE-B3 cells, effect that was prevented by the Cx-mimetic peptide TAT-Gap19 but not by Akt inhibitor. Altogether, these findings strongly suggest a contribution of hemichannels opening in the cell death induced by LA in HLE-B3 cells. These cells can be an excellent tool to develop pharmacological studies in vitro.